Stable Epigenetic Programming of Effector and Central Memory CD4 T Cells Occurs Within 7 Days of Antigen Exposure In Vivo - Bevington, Sarah L.; Fiancette, Remi; Gajdasik, Dominika W.; Keane, Peter; Soley, Jake K.; Willis, Claire M.; Coleman, Daniel J. L.; Withers, David R.; Cockerill, Peter N. (Frontiers in Immunology, 2021)
T cell immunological memory is established within days of an infection, but little is known about the in vivo changes in gene regulatory networks accounting for their ability to respond more efficiently to secondary infections. To decipher the timing and nature of immunological memory we performed genome-wide analyses of epigenetic and transcriptional changes in a mouse model generating antigen-specific T cells. Epigenetic reprogramming for Th differentiation and memory T cell formation was already established by the peak of the T cell response after 7 days. The Th memory T cell program was associated with a gain of open chromatin regions, enriched for RUNX, ETS and T-bet motifs, which remained stable for 56 days. The epigenetic programs for both effector memory, associated with T-bet, and central memory, associated with TCF-1, were established in parallel. Memory T cell-specific regulatory elements were associated with greatly enhanced inducible Th1-biased responses during secondary exposures to antigen. Furthermore, memory T cells responded in vivo to re-exposure to antigen by rapidly reprograming the entire ETS factor gene regulatory network, by suppressing Ets1 and activating Etv6 expression. These data show that gene regulatory networks are epigenetically reprogrammed towards memory during infection, and undergo substantial changes upon re-stimulation.